In vivo activation of PPAR target genes by RXR homodimers - IJpenberg, Annemieke (2004)
The ability of a retinoid X receptor (RXR) to heterodimerize with many nuclear receptors, including LXR, PPAR, NGF1B and RAR, underscores its pivotal role within the nuclear receptor superfamily. Among these heterodimers, PPAR:RXR is considered an important signalling mediator of both PPAR ligands, such as fatty acids, and 9-cis retinoic acid (9-cis RA), an RXR ligand. In contrast, the existence of an RXR/9-cis RA signalling pathway independent of PPAR or any other dimerization partner remains disputed. Using in vivo chromatin immunoprecipitation, we now show that RXR homodimers can selectively bind to functional PPREs and induce transactivation. At the molecular level, this pathway requires stabilization of the homodimer–DNA complexes through ligand-dependent interaction with the coactivator SRC1 or TIF2. This pathway operates both in the absence and in the presence of PPAR, as assessed in cells carrying inactivating mutations in PPAR genes and in wild-type cells. In addition, this signalling pathway via PPREs is fully functional and can rescue the severe hypothermia phenotype observed in fasted PPARα(−/−) mice. These observations have important pharmacological implications for the development of new rexinoid-based treatments.